Implementation of Internal Quality Assurance System in Improving the Quality of Education - Syamsul Rijal; Khoirul Anwar (Global Education Journal, 2026)
Educational quality assurance has become a strategic priority in improving school effectiveness and ensuring sustainable educational excellence. In the context of Integrated Islamic Schools, quality assurance must not only address academic achievement but also encompass religious competence and character development. This study aims to analyze the implementation of the Internal Quality Assurance System (SPMI) in improving educational quality at SMP IT Imam Syafi'i Samarinda, Wahdah Islamiyah Islamic Boarding School, East Kalimantan. The research employed a qualitative case study approach, with data collected through interviews, observations, and document analysis involving school leaders, teachers, and quality assurance personnel. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that SPMI has been implemented systematically through the PPEPP cycle, integrating National Education Standards with the Special Quality Standards of the Integrated Islamic School Network (JSIT). Quality improvement is reflected in curriculum integration, the strengthening of the tahfidz Al-Qur’an program, Islamic character development, teacher professional development, and continuous evaluation mechanisms. The study further demonstrates that quality assurance functions not merely as an administrative requirement but as an organizational strategy for fostering a sustainable culture of quality.